Is There Indigenous Governance in Coastal Tourism Village Management? - Ike Wanusmawatie; Shinta Fatimah Durrety; Ulvi Rohmatul Khasanah (Indonesian Association for Public Administration, 2026)
Management in coastal tourism villages has become increasingly complicated because it requires the harmonization of different elements, such as the economy, society, and the environment. For instance, if indigenous governance exists in a communi- ty, management of the village becomes increasingly complicated. This study seeks to explore the facilitation of management by the indigenous governance concept. This study seeks to establish how the concepts of participation and local wisdom in indigenous governance affect management success. Academically, this study seeks to establish gaps in the literature on indigenous governance in tourism management. From a practical perspective, this study seeks to provide the necessary information for decision-making. A mixed method approach will be adopted to undertake this research by analyzing data qualitatively and quantitatively using 44 articles available in Scopus. As revealed by quantitative content analysis, indigenous governance is not related to management success (Asymp. Sig. = 0.546). Numerous other variables have a greater impact on success. Nevertheless, indigenous governance recognizes, governs, and ensures the sustainability of the Dringu community.